A qualitative risk assessment of cleansing and disinfection requirements after an avian influenza outbreak in commercial poultry. Issue 6 (2nd November 2019) - Horigan, V.; Gale, P.; Adkin, A.; Brown, I.; Clark, J.; Kelly, L.
ABSTRACT: 1. During an avian influenza (AI) outbreak in the United Kingdom, the joint aim of the poultry industry and the Government is to eliminate and prevent the spread of infection, through control measures based on the current European Union (EU) Council Directive (2005/94/EC). An essential part of these measures is the cleansing and disinfection (C&D) of infected premises. 2. This risk assessment assessed the differences in re-infection in a repopulated flock if the EU Directive is interpreted to permit secondary C&D to be undertaken either with or without dismantling complex equipment. The assessment estimated the probability of virus survival on different types of equipment in a depopulated contaminated poultry house before and after preliminary and secondary C&D procedures. A risk matrix spreadsheet tool was used to carry out the assessment and concluded that, provided secondary C&D is carried out with due diligence (i.e. carried out to a defined code of practice as agreed by both industry and policymakers), the risk of re-infection from equipment is negligible, both with and without dismantling complex equipment in all farm types considered. 3. By considering the equipment types individually, the assessment identified those areas of the house which may still contain viable virus post-preliminary C&D and on which attention should be focussed during secondary C&D. The generic risk pathway and matrix spreadsheet tool have the potential to be used for other pathogens and species, given appropriate data.